2022
DOI: 10.1186/s12885-022-09196-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of docetaxel schedule on treatment tolerability and efficacy in patients with metastatic breast cancer: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Administration of single-agent docetaxel in a weekly schedule may offer similar efficacy, with a more favorable toxicity profile, compared to a three-weekly schedule in patients with metastatic breast cancer. Methods The original search of Medline, Embase, and Scopus was performed in September 2018 and references were updated with additional searches up to January 2021. Two reviewers independently screened the identified literature based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Remarkably, relatively few cases of severe hematological toxicity were observed in Phase I studies with oral docetaxel compared with incidences reported with both i.v. docetaxel, where hematological toxicity is dose limiting [24,41,42]. Potentially, there is a discrepancy between the in vitro and in vivo sensitivity of myeloid and lymphoid cells which may be the result of differences in drug exposure due to the spatial organization of the bone marrow or of protective effects of other cells present in the bone marrow microenvironment [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, relatively few cases of severe hematological toxicity were observed in Phase I studies with oral docetaxel compared with incidences reported with both i.v. docetaxel, where hematological toxicity is dose limiting [24,41,42]. Potentially, there is a discrepancy between the in vitro and in vivo sensitivity of myeloid and lymphoid cells which may be the result of differences in drug exposure due to the spatial organization of the bone marrow or of protective effects of other cells present in the bone marrow microenvironment [43].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, relatively few cases of severe hematological toxicity were observed in Phase I studies with oral docetaxel compared with incidences reported with both i.v. docetaxel, where hematological toxicity is dose limiting [24,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse effects are represented by of neutropenia, febrile neutropenia, neuropathy, onycholysis, epiphora, and toxicity, often leading to treatment discontinuation. Moreover, docetaxel is a highly lipophilic drug with very poor water solubility and instability [ 170 ]. Cabazitaxel is a recent taxoid agent showing in vitro and in vivo activity against cell lines and tumors resistant to docetaxel and paclitaxel [ 171 ].…”
Section: Breast Cancer Therapiesmentioning
confidence: 99%
“…[11][12][13] Due to its therapeutic index, docetaxel, a microtubuletargeting agent, has garnered significant attention in cancer chemotherapy. 14 Docetaxel, a taxane oncology drug, exhibits cytotoxic potential and clinical efficacy against various malignancies, including breast, lung, and ovarian cancers. It induces tubulin monomer polymerization, inhibits depolymerization, and causes G2/M cell cycle arrest during mitosis, ultimately leading to cell death.…”
Section: Introductionmentioning
confidence: 99%